2014
DOI: 10.7196/samj.7655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adherence to national treatment guidelines among tuberculosis patients in three provinces of South Africa

Abstract: Background Standardised tuberculosis (TB) treatment through directly observed therapy (DOT) is available in South Africa, but the level of adherence to standardised TB treatment and its impact on treatment outcomes is unknown. Objectives To describe adherence to standardised TB treatment and provision of DOT, and analyse its impact on treatment outcome. Methods We utilised data collected for an evaluation of the South African national TB surveillance system. A treatment regimen was considered appropriate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…We also determined that one-third of prescribed regimens in our study (33%, 29/88) did not appear to follow national treatment guidelines. While lower rates of inappropriate regimens in children <8 years of age (11%) have been reported in other studies from SA, [7] the use of inappropriate regimens is known to be a relatively widespread problem [26] and can contribute to both treatment failure and the development of drug resistance. [27] A systematic review has found that inadequate knowledge of national treatment guidelines among healthcare workers is also relatively common, although the review did not include any literature from SA.…”
Section: Researchmentioning
confidence: 84%
See 1 more Smart Citation
“…We also determined that one-third of prescribed regimens in our study (33%, 29/88) did not appear to follow national treatment guidelines. While lower rates of inappropriate regimens in children <8 years of age (11%) have been reported in other studies from SA, [7] the use of inappropriate regimens is known to be a relatively widespread problem [26] and can contribute to both treatment failure and the development of drug resistance. [27] A systematic review has found that inadequate knowledge of national treatment guidelines among healthcare workers is also relatively common, although the review did not include any literature from SA.…”
Section: Researchmentioning
confidence: 84%
“…[25] A small cohort drawn from three provinces in 2009 showed slightly higher rates of treatment success (88%, 65/74) in children <8 years of age. [7] A record review of children (aged 0 -15 years) living in periurban communities found that treatment success was good (79%, 65/82 in 2008 -2011) among patients receiving supervised home visits from trained community caregivers or nurses, but clinic-based treatment showed relatively low rates of success (54%, 52/97 in 2005 -2008) and high rates of loss to follow-up (38%). [8] In comparison, older studies (2003 -2005) of hospital-based treatment in Cape Town reported treatment success of 71% (97/137) in HIV-infected children (aged 0 -11 years), [9] and higher mortality in young children (9%, 31/334, age <3 years) than older children (4%, 10/262, age 4 -13 years), although treatment outcomes were not reported separately from patients who tested positive for drug resistance (11%).…”
Section: Discussionmentioning
confidence: 99%
“…Health education is integrated into services provided at primary health care (PHC) level in South Africa [15]. However, inadequate patient counselling on treatment expectations [16,17] and inconsistent implementation of the Directly Observed Treatment, Short Course (DOTS) strategy [18,19] continue to exacerbate TB treatment LTFU. Apart from South Africa, similar findings of poor patientprovider communication hindering TB treatment completion have been demonstrated as far afield as Eritrea, Tanzania, Pakistan and Ethiopia; always with the discussion prioritizing strengthened patient-provider trust and treatment literacy [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Data from Gauteng, KwaZulu-Natal and Mpumalanga provinces in 2009 indicated that while nearly all patients (97%) received DOT support through the intensive phase of treatment, only 60% of patients received DOT support throughout the full treatment course. [6] Objective To contribute to the evidence base on public sector TB treatment service delivery, we constructed a retrospective cohort of adult TB patients treated at three public sector clinics in the city of Johannesburg. Using medical record data, we report patient characteristics, HIV status and TB history, diagnosis and laboratory information, treatment characteristics, DOT supervision and treatment outcomes for this cohort.…”
mentioning
confidence: 99%